Blue Light from Cell Phones Can Cause Chronic Retinal Light Injury: The Evidence from a Clinical Observational Study and a SD Rat Model. (17th May 2021) - Li, Huili; Zhang, Ming; Wang, Dahong; Dong, Guojun; Chen, Zhiwei; Li, Suilin; Sun, Xiaohong; Zeng, Min; Liao, Haiyang; Chen, Huifang; Xiao, Shengyan; Li, Xiaodan
Abstract : Background . To investigate the chronic photodamage induced by the low-intensity blue light of phones, we carried out a clinical pilot study and established an animal model by irradiating SD rats with a homemade illuminator. Methods . Clinical investigation: A total of 25 clinical medical workers in our hospital were selected and divided into a control group and an observation group according to the daily video terminal use time. Multifocal electrophysiological system (Mf-ERG) was used for retinal functional examination. Animal experiment: A total of sixty SD rats were randomly divided into a control group (n = 6 ) and an experimental group (n = 54 ). The experimental rats were divided into nine groups, which were exposed to the blue light illuminator of the simulated cell phone array for different time. The visual electrophysiology of the rats was tested, and changes in structure were observed by H&E staining and transmission electron microscopy. Results . In clinical investigation, macular centers near the concave area retinal photoreceptor cells have reduced amplitude. In animal experiments, the amplitude of photoreceptor cells decreased, the peak time was delayed, and the amplitudes were lower in the experimental groups. H&E staining and transmission electron microscope showed retinal tissue structure and functional damage in experimental groups. Conclusions . Long-term exposure to low-illuminance blue light can cause retinal tissue structure and functional damage, and the chronic damage due to low-illuminance light warrants attention. The clinical registration number is 2018-KY-KS-LHL.